Profitability of high value crops with organic nitrogen sources under rice (Oryza sativa) based cropping sequence - YADAV, S K; BABU, SUBHASH; YADAV, M K; SINGH, YOGESHWAR; SINGH, KALYAN (The Indian Journal of Agricultural Sciences, 2014)
A field experiment was conducted during 2005-06 and 2006-07 at Campus Research Farm, Institute of Agricultural Sciences, Banaras Hindu University, Varanasi to identify a suitable high value cropping sequence with organic nitrogen sources under rice (Oryza sativa L.) based cropping system. The experiment was laid out in split plot design with three replications. Seven rice based cropping sequences, viz. rice-potato-onion; rice-green pea-onion; rice-potatocowpea (green pod); rice-green pea-cowpea; rice-rajmash (green pod)-onion; rice-rajmash-cowpea and rice-maize (green cob)-cowpea were assigned to main plots and three organic treatments (control; 100% RDN through organic manure along with biofertilizers and 100% RDN through organic manure alone) were allocated to sub plots. Among the cropping sequences, rice-potato-onion gave the highest rice grain equivalent yield (35.57 tonnes/ha), maximum net return (Rupees 268 656/ha), profitability (Rupees 738/ha/day) and labour employment generation (469 man days/ha/year). However rice yield and soil fertility status was not significantly affected by cropping sequences. Application of 100% recommended dose of through organic manure along with biofertilizers (Azotobacter and PSB) had the highest rice equivalent grain yield (35.31 tonnes/ha), production efficiency (96.74 kg/ha/day), net monetary return (Rupees 292 454/ha), profitability (Rupees 803/ha/day) and labour employment generation (419 man days/ha/year). Inclusion of pulses in sequence with proved superior due to its viable favorable effect on soil fertility. Thus organic nitrogen nutrition with biofertilizers had the highest rice equivalent grain yield, production efficiency, net monetary return and profitability.